2021
DOI: 10.3389/fmars.2021.715078
|View full text |Cite
|
Sign up to set email alerts
|

Using Glycerol to Produce European Sea Bass Feed With Oleaginous Microbial Biomass: Effects on Growth Performance, Filet Fatty Acid Profile, and FADS2 Gene Expression

Abstract: Using a circular economy concept, the present study investigated the use of crude glycerol, a primary by-product of biodiesel production, as a low-priced nutrient source for heterotrophic cultivation of the fungus-like protist Schizochytrium limacinum SR21 strain. The whole biomass of this oleaginous microorganism, rich in docosahexaenoic acid (DHA) and high-quality proteins, was then paired with a vegetable oil (VO) source and used to replace fish oil (FO) in European sea bass (Dicentrarchus labrax) feeds. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Fillets of extensive reared sea bass showed the lowest value of C16:1n9 (p = 0.002), C16:1n7 (p = 0.006), C17:1 (p = 0.002), C18:1n7 (p = 0.005), and the highest (p = 0.005) value of oleic acid (C18:1 n9), who was identified as the major monounsaturated fatty in cultured and wild sea bass [37][38][39].…”
Section: Fatty Acid Profiles Of Filletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fillets of extensive reared sea bass showed the lowest value of C16:1n9 (p = 0.002), C16:1n7 (p = 0.006), C17:1 (p = 0.002), C18:1n7 (p = 0.005), and the highest (p = 0.005) value of oleic acid (C18:1 n9), who was identified as the major monounsaturated fatty in cultured and wild sea bass [37][38][39].…”
Section: Fatty Acid Profiles Of Filletsmentioning
confidence: 99%
“…There is a need of a deeper understanding and knowledge on the fatty acid composition and the natural diet of the fish which lives in the salt lake to confirm this hypothesis. The use of formulated feeds rich in n-3 PUFA in aquaculture-desirable from a human nutritional standpoint in consideration of the role played by n-3 PUFA in the prevention of cardiovascular and inflammatory diseases-also has a positive incidence on the growth rate and feed conversion efficiency of fish [14,39].…”
Section: Fatty Acid Profiles Of Filletsmentioning
confidence: 99%
“…In addition, the host G. haimaensis parasitized by B. pettiboneaei displayed significant changes in the expression of genes involved in lipid metabolism, such as FADS2 (fatty acid desaturase 2, FC = 1.0167, p = 7.82E-05). FADS2 encodes a protein that is involved in the biosynthesis of unsaturated fatty acids and plays an important role in lipid anabolism, as the first enzyme in the biosynthesis of long-chain fatty acid (≥C20; Terova et al, 2021 ). Similarly, the rate-limiting enzyme diacylglycerol o-acyltransferase in cotton melon aphids parasitized by Lysiphlebia japonica has been found to increase by 3.24 fold, and almost all key genes in the glycerolipid synthesis pathway have been found to be up-regulated with respect to the non-parasitic group ( Zhang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in DHA/AA between the two groups could be probably explained by the differences in feeding. In the last decade, the feeding industry has promoted the use of ingredients for aquaculture feeding that can improve the levels of ω3 fatty acids and in particular DHA [ 20 ]. However, some studies reported the importance of supplying fish diets not only with ω3-3 PUFA but also with ω6-PUFA to improve growth performance and immune system function [ 21 ].…”
Section: Resultsmentioning
confidence: 99%